Partial replacement of cement with incinerated sewage sludge ash (ISSA) in mortar brick with natural calcium carbonate as additive - Lwee, Kui Choo (2016)
Nowadays, sewage sludge has become one of the largest contributors towards solid waste in Malaysia and this number is going to increase in future. The world population expected to grow and also the increase in the volume of waste water shows that the sewage sludge ash will rise at a very fast pace in the next year. As the current disposable way for sewage sludge is through landfill, it had caused Malaysia facing the solid waste management problem as we are running out of landfill site. The cost for collecting and disposing the sewage sludge had been an issue all this while to our government and soon it will become a burden to our country. Studies had been conducted on sewage sludge as potential partial cement replacement in mortar and concrete. A further investigation is needed of eggshell powder as potential additive in mortar brick. The sewage sludge was obtained from Indah Water Konsortium (IWK) sewage plant in Kuantan. Organic materials in the sewage sludge were removed through incineration at the temperature of 800˚C with the period of 3 hours. In this investigation, four different percentage of eggshell powder with 10% of Incinerated Sewage Sludge Ash (ISSA) were added into the mortar brick. The materials used were Ordinary Portland Cement, fine aggregates, ISSA and eggshell powder. From the investigation, the results of 10% ISSA partial cement replacement with different percentage of raw eggshell powder as additive were compared in the aspect of compressive strength, flexural strength and water absorption.